Evaluating Impacts of a Leading Pedestrian Signal on Pedestrian Crossing Conditions at Signalized Urban Intersections: A Field Study - Gitelman, Victoria; Carmel, Roby; Pesahov, Fany (Frontiers in Sustainable Cities, 2020)
Signalized intersections appear among urban locations with a high frequency of pedestrian injury. Due to the need to move large traffic volumes, a shared vehicle-pedestrian green phase is generally applied for turning vehicles and crossing pedestrians at intersections on busy urban roads. The shared green relies on a driver’s ability to yield to crossing pedestrians which, if it fails, may increase the risk of pedestrian injury. A solution suggested for improving pedestrian safety in such situations is to provide a leading pedestrian signal, i.e. the pedestrian green appears earlier than the vehicle green, forcing vehicles to give priority to the pedestrians already on the crossing. A field-study was conducted at two intersections in Tel-Aviv, Israel, to examine the impact of such a measure on pedestrian crossing conditions. The pedestrian green phase was brought forward by 3 seconds. The study analyzed changes in road user behaviors, in the crosswalk area, in the after period when the measure was activated compared to the before period. The results showed that following the measure’s application, the percentage of traffic lights’ cycles with giving-right-of-way to all pedestrians, at the beginning of green, increased to 97%-100% for pedestrians crossing from the sidewalk and to 94%-99% for those who crossed from the road median. In addition, improvements were observed in the provision of pedestrian right-of-way during the whole green phase. The measure did not affect the rate of vehicle-pedestrian conflicts due to low conflict occurrence at the study sites. Overall, the findings indicated positive changes in pedestrian crossing conditions, following the introduction of a leading pedestrian green. The increase in giving-right-of-way to pedestrians by turning vehicles is expected to contribute to improved pedestrian safety while crossing at signalized intersections.